Evading stability-biocompatibility tradeoff in TiNb coatings with armour-like super hydrophilic micro-nano structure surface - Yu Zheng; Peng Xu; Long Li; Qibin Liu (Journal of Materials Research and Technology, 2023)
Modification of micro-nano structures on the surface of medical implants using a femtosecond laser (FSL) can improve cell behavior, increase tissue and material bonding strength, and promote preferred osseointegration. Nevertheless, the FSL processed micro-nano structures suffer from a compromise between biocompatibility and structural stability. Herein, a Ti32·5Nb alloy laser cladding (LC) coating was initially created on the surface of the Ti6Al4V (TC4) substrate, followed by the construction of an armour-like micro-nano structure with structural stability and biocompatibility on the coating surface. The results show that the microhardness, were resistance and corrosion resistance of the coatings were significantly improved. It efficiently prevents wear damage to the micro-nano structure by modifying the surface armour structure of FSL. In addition, a considerable quantity of hydroxyapatite (HA) is deposited on the surface, resulting in a Ca/P ratio that is closer to that of osteogenesis. Moreover, the surface structure is a periodic micro-nano structure with three-level distribution, which can guide the migration and proliferation of cell nanofiber matrix. Human osteosarcoma cells (MG-63) adhere to the surface and proliferate rapidly along the direction of the micro-nano structure. Hereby, the armoured micro-nano structures developed exhibit sustained wear resistance and great biocompatibility. It offers a wide range of applications in the field of surface modification of orthopedic biomaterials.